Perihelion Activity of (3200) Phaethon is Not Dusty: Evidence from STEREO/COR2 Observations - Man-To Hui (The Astronomical Journal, 2023)
We present an analysis of asteroid (3200) Phaethon using coronagraphic observations from 2008 to 2022 by the COR2 cameras onboard the twin Solar TErrestrial RElations Observatory spacecraft. Although undetected in individual images, Phaethon was visible in stacks combined from the same perihelion observations, yet only at small (≲30°) but not large (≳150°) phase angles. The observations are in line with the contribution from a bare nucleus, thereby seriously contradicting the interpretation based on HI-1 observations that attributes the perihelion activity to the ejection of μ m-sized dust. We obtained an upper limit to the effective cross section of μ m-sized dust to be ≲10 ^5 m ^2 , at least three orders of magnitude smaller than earlier estimates based on HI-1 data. On the contrary, the COR2 observations cannot rule out the existence of mm-sized or larger debris around Phaethon. However, the fact that no postperihelion debris tail has ever been detected for Phaethon suggests the unimportance of such dust in the perihelion activity. We thus conclude that the perihelion activity of Phaethon is highly unlikely relevant to the ejection of dust. Rather, we deduce that the activity is associated with gas emissions, possibly Fe i and/or Na D lines. To verify our conjecture and to fully understand the perihelion activity of Phaethon, more observations at small heliocentric distances are desired. We compile a list of observing windows ideal for the search of gas emissions of the asteroid from ground telescopes. The best opportunities will be during total solar eclipses.